(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Migraine causes difficulties in daily life. Objective: The purpose of this present study was to assess the severity of migraine associated with comorbidities. Methodology: This cross sectional study was carried out in Headache Clinic and Neurology outdoor in the Department of Neurology at Dhaka Medical College and Hospital (DMCH), Dhaka during the period of July 2010 to June 2011 for a period of one (01) year. All the patients presented with migraine were included as study population who were divided into two groups. Migraine patients without comorbidities were designated as group I and with comorbidities were in group II. The comorbidities were assessed which were both physical as well as psychiatric. The severity of migraine was assessed on the basis of four principal components like pain intensity, nausea, disability and tolerability. Result: A total of 70 patients with migraine were recruited of which 37 patients were in group I and 33 patients were in group II. In group II major depressive disorder was in 8(24.3%) cases, generalized anxiety disorder was in 6(18.1%) cases and hypertensive was in 7(21.2%) cases. Among 8 major depressive disorder patients, mild, moderate and severe migraines were found in 1(3.03%) cases, 2(6.06%) cases and 5(15.15%) cases respectively. Out of 6 GAD patients, mild, moderate and severe migraine were found in 1(3.03%) case, 1(3.03%) case and 4(12.12%) cases. Seven patients were hypertensive of which 1(3.03) patient had mild, 2(6.06%) had moderate and 4(12.12%) had severe migraine. Mild migraine was found in 18(48.6%) patients in group I and 6(18.2%) patients in group II. Moderate migraine was found in 12(32.5%) patients and 8(24.2%) in group I and group II respectively. Severe migraine was found in 7(18.9%) patients in group I and 19(57.6%) patients in group II. Conclusion: Severity of migraine is associated with different physical and psychiatric comorbidities. Journal of National Institute of Neurosciences Bangladesh, 2015;1(2): 33-36